Clinical characteristics and results of laser peripheral iridotomy of pigment dispersion syndrome - Bayraktar, Şerife; Çağman, Selver Selen; İzgi, Belgin and Örekici Temel, Gülhan (Journal of Surgery and Medicine, 2017)
Aims: To report the clinical findings, characteristics and the results of peripheral laser iridotomy in pigment dispersion syndrome (PDS) patients. Methods: Medical records of 30 patients who had been diagnosed with PDS were evaluated retrospectively at Glaucoma Department of Istanbul Faculty of Medicine at Istanbul University. Results: Sixty eyes of these 30 patients enrolled in the study. 18 of them (60%) were male and 12 (40%) were female with mean age of 42.4 ±12.3 years (range: 22 to 73 years). Forty-six eyes of the 23 patients had myopia, 12 eyes of 6 patients had hyperopia, 2 eyes of 1 patient had emmetropia. All patients except 2 eyes of the 1 patient had (96.6%) Krukenberg spindles. Homogeneous trabecular meshwork(TM) pigmentation was seen in all patients. Thirty-two eyes of 17 patients (53.3 %) had iris transillumination defects. Neodymium:yttrium–aluminum–garnet (Nd:YAG) peripheral laser iridotomy was performed in 44 eyes of 60 eyes (73.3%). Conclusion: The most common clinical findings in Turkish PDS patients were Krukenberg spindles and homogeneous TM pigmentation. If PDS hasn’t advanced in pigmentary ocular hypertension or pigmentary glaucoma, progression can be stabilized by laser iridotomy and medical treatment.